THE APPRAISAL OF ELECTROBIOLOGICAL ACTIVITY OF THE GASTROINTESTINAL TRACT AMONG CHILDREN AND THE SELECTION OF THE DRUG THERAPY - A.P. Ponomareva; S.V. Bel'mer; L.M. Karpina (Вопросы современной педиатрии)
The method of the peripheral electrogastroenteromyography has been used for appraisal of the motor function among 85 children (44 girls, 41 boys) aged between 6 and 15 years old with chronic gastroduodenitis at the stage of recrudescence (I group — 45 children), chronic gastroduodenitis without recrudescence (II group — 20 children), peptic ulcer disease at the stage of recrudescence (III group — 10 children) and chronic duodenal obstruction related in most cases to arteriomesen teric compression (iv group — 10 children). Palpable changes in electrogastroentrerography indices were noted only among children with chronic duodenal obstruction and manifested as the increase of electrobiological activity after taking the medication along with the reduction of the indices, which showed the contractive activity itself. Taking of the medications differentially affects the electrogastroentrerography indices: domperidone increases both electro biological activity itself and myo electrical activity, whereas mebeverine decreases them, acting as not only a spasmolysant but also a motility modulator.Key words: electrobiological activity, chronic gastroduo denitis, peptic ulcer disease, children.